Cholecystectomy is associated with dysglycaemia: Cross‐sectional and prospective analyses. Issue 8 (25th May 2022) - Sang, Miaomiao; Xie, Cong; Qiu, Shanhu; Wang, Xuyi; Horowitz, Michael; Jones, Karen L.; Rayner, Christopher K.; Sun, Zilin; Wu, Tongzhi
Abstract: Cholecystectomy has been reported to be associated with increased risk of diabetes in cross‐sectional studies. In the current study, we performed both cross‐sectional and prospective analyses to examine the association between cholecystectomy and dysglycaemia in Chinese community‐dwelling adults. A total of 1612 participants (n = 1564 without cholecystectomy and n = 48 with cholecystectomy) were evaluated for glycaemic status (according to the World Health Organization (WHO) 1999 criteria) and then followed up over ~3.2 years. Percent changes (Δ) in fasting blood glucose and HbA1c from baseline at the follow‐up visit were calculated to define glycaemic control as stable (−10% ≤ Δ < 10%), improved (Δ < −10%), or worsened (Δ ≥ 10%). The baseline cross‐sectional analyses indicated that cholecystectomy was associated with an increased risk of both prediabetes and diabetes, while the prospective analysis indicated that cholecystectomy was also associated with a greater risk of deterioration in glycaemic control (ΔFPG ≥10% and ΔHbA1c ≥10%) ( P  < 0.05 for each, both before and after adjusting for potential confounding covariates). These observations suggest that individuals in the Chinese community‐dwelling population who have undergone cholecystectomy are at increased risk of dysglycaemia. Further studies are warranted to both delineate the underlying mechanisms and to clarify whether more intense surveillance for future development of diabetes is needed in this group.